2015
DOI: 10.18632/oncotarget.4385
|View full text |Cite
|
Sign up to set email alerts
|

Prokineticin 2 (PROK2) is an important factor for angiogenesis in colorectal cancer

Abstract: The Prokineticin 2 (PROK2) is correlated with indispensable in maintaining the homeostasis of healthy human tissues. Herein, we examined the role of PROK2 in human colorectal cancer.After total RNA extraction from 6 colorectal cancer cell lines, we examined the expression of PROK2 mRNA. For investigating angiogenesis and tumor growth in mice, the PROK2 gene was transfected into colorectal cancer cell lines having low PROK2 mRNA expression. In addition, small interfering RNA (siRNA) was transfected into colorec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Previous reports have demonstrated that inflammatory cytokines affect the microenvironment of existing cancer cells and facilitate the migration, invasion, and angiogenesis of cancer cells [ 35 , 36 ]. The findings of our present and previous study [ 21 ] show that PROK2 expression is highly correlated with angiogenesis, tumor formation, and liver metastasis through in vitro and in vivo assays. This suggests that in CRC, the tumor itself organizes the surrounding environment via PROK2 expression, which plays a significant role within the tumor microenvironment.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Previous reports have demonstrated that inflammatory cytokines affect the microenvironment of existing cancer cells and facilitate the migration, invasion, and angiogenesis of cancer cells [ 35 , 36 ]. The findings of our present and previous study [ 21 ] show that PROK2 expression is highly correlated with angiogenesis, tumor formation, and liver metastasis through in vitro and in vivo assays. This suggests that in CRC, the tumor itself organizes the surrounding environment via PROK2 expression, which plays a significant role within the tumor microenvironment.…”
Section: Discussionsupporting
confidence: 78%
“…The primer sequences for PROK2 (GenBank accession no. NM_021935) gene-coding regions were as follows: 5′ primer, PROK2-AX: 5′-GGGGATCCATGAGGAGCCTGTGCTGCGCCCCA-3′; 3′ primer, PROK2-BX: 5′-GGGAATTCCTTTTGGGCTAAACAAATAAATCG-3′ [ 21 ]. GAPDH was used as an internal PCR control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of PROK2 antagonist suppresses the tumorigenic processes through inhibiting angiogenic process in glioma and blocking myeloid cell infiltration in pancreatic cancer [ 10 ]. Colorectal cancer cells with PROK2 siRNA show a significant decrease in PROK2 expression and tumor growth in mice models [ 11 ]. MicroRNA-374a acts as tumor suppressor to inhibit cell proliferation, cell cycle progression, and cell invasion through targeting PROK2 in human glioma cells [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prokineticin 2 (PROK2), a member of prokineticin protein family, is a cysteine-rich secreted protein containing a conserved N-terminal sequence of AVITGA and 10 cysteines [ 9 ]. Studies have shown that PROK2 might be involved in tumorigenic processes through regulating angiogenesis in glioblastomas [ 10 ] and in colorectal cancer [ 11 ], myeloid cell infiltration in pancreatic cancer [ 12 ], growth in hepatocellular carcinoma [ 13 ] and tumor progression in prostate cancer [ 14 ]. PROK2 might be related to drug resistance of breast cancer and metastasis to lung [ 15 ].…”
Section: Introductionmentioning
confidence: 99%